PENGARUH MODEL QUANTUM WRITING BERBANTUAN MEDIA GAMBAR DALAM KETERAMPILAN MENULIS PUISI PADA SISWA KELAS VIII SMP SWASTA MARIA GORETTI KABANJAHE TAHUN PEMBELAJARAN 2024/2025 - Ginting, Dicky Alpredo; Liana; Candra Ronitua Gultom (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This study aims to determine the effect of the Quantum Writing learning model assisted by visual media on the poetry writing skills of Grade VIII students at SMP Swasta Maria Goretti Kabanjahe in the 2024/2025 academic year. The research employed a post-test-only control group design with a sample of 64 students, divided into two groups: 32 students in the experimental class and 32 in the control class. The research instruments consisted of a test and a perception questionnaire, both of which were validated by experts. The normality test showed that the data were normally distributed (Significance = 0.062 > 0.05), and the homogeneity test indicated that the data were homogeneous (Significance = 0.072 > 0.05). The average score from the perception questionnaire was 4.60 on a 5-point scale, indicating a very positive perception. The average poetry writing score of the experimental group was 88.96, while the control group scored 65.43, resulting in a difference of 23.53 points. The theme of motivation was the most frequently chosen by students in the experimental class. The ANOVA test revealed a significance value of 0.000 (< 0.05), indicating a significant effect of the model on learning outcomes. Additionally, the t-test produced a t-value of 13.224, which is greater than the critical t-value of 1.696, with a significance value of 0.000 (< 0.05). Thus, it can be concluded that the application of the Quantum Writing model assisted by visual media has a positive and significant effect on improving students’ poetry writing skills.